Women in the Hispanic American Press in Times of Revolution: The Cases of Lima, Caracas, Buenos Aires, and Santiago de Chile - Rivera, Monserratt; Morán, Daniel (Revista revoluciones, 2021)
On the eve of Peru's bicentennial and the current relevance that gender studies have acquired, we believe it is convenient to highlight the role played by the written press during the wars of independence carried out in the Hispanic viceroyalties. Specifically, the cases of Lima, Buenos Aires, Caracas and Santiago de Chile will be addressed. In this sense, we will be able to observe how the newspapers of the time aligned themselves on different sides (either royalist or patriot) and, making use of their influence on the population, made clear their positions regarding female education and the role that the fair sex should play during the patriotic struggles. This was part of a political stratagem to exercise social control, in which the beneficiaries were the power groups.
Keywords: Press; Hispanic America; Independence; female participation; vision of the woman